The Effect of Religiusity, Tranformational Leadership and Demography on Organizational Citizenship Behavior (OCB) - Annisa Ayu Budhiarti; Yunita Faela Nisa (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
Abstract This research was conducted to find out the significance of the influence of religiosity, transformational leadership style and demography on organizational citizenship behavior (OCB) on 138 state-owned employees in PT. Surveyor Indonesia and 88 private employees in the Household Pesticide Industry Company. Sampling conducted using non probability sampling. The measuring tool used in this study took from Huber (2012) figures to measure religiosity, Rafferty and Griffin (2014) to measure transformational leadership styles. Test the validity of measuring instruments using Confirmatory Factor Analysis (CFA) techniques and data analysis techniques using multiple regression analysis techniques. The results of this study indicate that there is a significant influence of religiosity, transformational leadership style and demography on organizational citizenship behavior (OCB) by contributing 26.2%. That is, the proportion of variance of organizational citizenship behavior explained together by religiosity, transformational leadership style and demography is 26.2% while the other 73.8% is influenced by other variables beyond this study. Abstrak Penelitian ini dilakukan untuk mengetahui signifikansi pengaruh religiusitas, gaya kepemimpinan transformasional dan demografi terhadap Organizational Citizenship Behavior (OCB) pada 138 karyawan BUMN di PT. Surveyor Indonesia dan 88 karyawan swasta di Perusahaan Industri Pestisida Rumah Tangga. Pengambilan sampel yang dilakukan menggunakan non probability sampling. Alat ukur yang digunakan dalam penelitian ini mengambil dari tokoh Huber (2012) untuk mengukur religiusitas, Rafferty dan Griffin (2014) untuk mengukur gaya kepemimpinan transformasional. Uji validitas alat ukur menggunakan teknik Confirmatory Factor Analysis (CFA) dan teknik analisis data menggunakan teknik analisis regresi berganda. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan dari religiusitas, gaya kepemimpinan transformasional dan demografi terhadap Organizational Citizenship Behavior (OCB) dengan memberikan kontribusi sebesar 26,2%. Artinya, proporsi varians dari organizational citizenship behavior yang dijelaskan secara bersama-sama oleh religiusitas, gaya kepemimpinan transformasional dan demografi adalah sebesar 26,2% sementara 73,8% lainnya dipengaruhioleh variabel lain diluar penelitian ini. DOI : 10.15408/jp3i.v6i2.9160